SDG Impact Index with Double Materiality Perspective: Evidence from OECD Commercial Bank Industry - Aras, Guler; Furtuna, Ozlem Kutlu; Kazak, Evrim Hacioglu (SPRINGER, 2024)
The soundness and healthy functioning of financial institutions that contribute to sustainable development by channeling savings into investments has a direct impact on the economy as a whole. The Sustainable Development Goals (SDGs) cannot be achieved without the strong support of the financial services industry. The novelty of this study is that it investigates the SDGs with ESG indicators through a double materiality perspective for 1888 companies from the OECD financial institutions. This study shows how commercial banks can identify and prioritize the SDGs and targets and how sustainable practices at the corporate level can contribute to achieving these global goals by adopting a sound methodological approach. The empirical results indicate a significant variation between three perspectives including financial materiality, double materiality, and double materiality with fuzzy logic and some of the SASB issues and GRI issues are more material to a particular SDG than others. There are few studies that focus on developing such a multi-perspective methodology, and this study further contributes to the existing knowledge by shedding light on the SDG Impact Index of commercial banks' with double materiality perspective. In this context, this paper aims to explore the impact of material issues for the OECD financial services industry to achieve the 2030 Agenda's goal of leaving no one behind.
Keywords: SDG impact index; Mapping analysis; Double materiality; Commercial banking industry; Principal component analysis; Fuzzy logic; SUSTAINABLE DEVELOPMENT GOALS; CORPORATE SUSTAINABILITY; SECTOR; RELEVANCE; Social Sciences - Other Topics; Sociology